Genetic Pharmacotherapy as an Early CNS Drug Development Strategy: Testing Glutaminase Inhibition for Schizophrenia Treatment in Adult Mice - Mingote, Susana; Masson, Justine; Gellman, Celia; Thomsen, Gretchen M.; Lin, Chyuan-Sheng; Merker, Robert J.; Gaisler-Salomon, Inna; Wang, Yvonne; Ernst, Rachel; Hen, René; Rayport, Stephen (Frontiers in Systems Neuroscience, 2016)
Genetic pharmacotherapy is an early drug development strategy for the identification of novel CNS targets in mouse models prior to the development of specific ligands. Here for the first time, we have implemented this strategy to address the potential therapeutic value of a glutamate-based pharmacotherapy for schizophrenia involving inhibition of the glutamate recycling enzyme phosphate-activated glutaminase. Mice constitutively heterozygous for GLS1, the gene encoding glutaminase, manifest a schizophrenia resilience phenotype, a key dimension of which is an attenuated locomotor response to propsychotic amphetamine challenge. If resilience is due to glutaminase deficiency in adulthood, then glutaminase inhibitors should have therapeutic potential. However, this has been difficult to test given the dearth of neuroactive glutaminase inhibitors. So, we used genetic pharmacotherapy to test the therapeutic potential of glutaminase inhibition. We specifically asked whether adult induction of GLS1 heterozygosity would attenuate amphetamine responsiveness. We generated conditional floxGLS1 mice and crossed them with global CAG ERT2 cre/+ mice to produce GLS1 iHET mice, susceptible to tamoxifen induction of GLS1 heterozygosity. One month after tamoxifen treatment of adult GLS1 iHET mice, we found a 50% reduction in GLS1 allelic abundance and glutaminase mRNA levels in the brain. While GLS1 iHET mice showed some recombination prior to tamoxifen, there was no impact on mRNA levels. We then asked whether induction of GLS heterozygosity would attenuate the locomotor response to propsychotic amphetamine challenge. Before tamoxifen, control and GLS1 iHET mice did not differ in their response to amphetamine. One month after tamoxifen treatment, amphetamine-induced hyperlocomotion was blocked in GLS1 iHET mice. The block was largely maintained after 5 months. Thus, a genetically induced glutaminase reduction — mimicking pharmacological inhibition — strongly attenuated the response to a propsychotic challenge, suggesting that glutaminase may be a novel target for the pharmacotherapy of schizophrenia. These results demonstrate how genetic pharmacotherapy can be implemented to test a CNS target in advance of the development of specific neuroactive inhibitors. We discuss further the advantages, limitations, and feasibility of the wider application of genetic pharmacotherapy for neuropsychiatric drug development.